The Lived Experiences of Iranian Older Adults With Empty Nest Syndrome: A Phenomenological Study - Abdolbaset Mahmoudpour; Asyie Shariatmadar; Ahmad Borjali; Abdollah Shafiabadi (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives Empty nest syndrome (SEN) in Iranian older adults is becoming an important social phenomenon. Although it is not a clinical disorder, it can affect a person's life and lead to depression, alcoholism, marital conflicts, and identity crisis. This study aims to explore the lived experiences of older adults with SEN in Iran. Methods & Materials This is a qualitative phenomenological study. Participants were 17 older adults with a mean age of 65.7 years (6 males and 11 females) suffering from ENS in Tehran, Iran, in 2022. Sampling was done purposefully and until reaching theoretical saturation. Semi-structured interviews were used to collect data regarding lived experiences. Results Six main themes (existential crisis, emotional turmoil, cognitive disorientation, functional decline, disruption in interpersonal relationships, and satisfaction with the transition period) and 23 sub-themes were extracted. Conclusion Understanding of Iranian older adults' experiences of ENS can provide valuable insights to gerontologists and practitioners in fields of psychology, counseling, and social work to develop future interventions for these older adults and enhance their quality of life.